14-Th IEEE International Conference on Peer-to-Peer Computing 2014
DOI: 10.1109/p2p.2014.6934310
|View full text |Cite
|
Sign up to set email alerts
|

Replicated erasure codes for storage and repair-traffic efficiency

Abstract: This paper introduces a new family of redundancy schemes for distributed storage systems, called replicated erasure codes (REC), which combine the storage-space efficiency of erasure codes and the repair-traffic efficiency of replication. A formal model for analyzing the storage and repair-traffic costs under availability and persistency constraints is also developed. It is shown that under parameters that characterize common P2P environments, REC generally achieves better results than each of the two methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The amount of storage affects the number of chunk erasures in the system and the repair degree indicates the number of chunks sent in order to repair one erased chunk. Therefore, a repair efficient scheme must minimize both [13].…”
Section: Resultsmentioning
confidence: 99%
“…The amount of storage affects the number of chunk erasures in the system and the repair degree indicates the number of chunks sent in order to repair one erased chunk. Therefore, a repair efficient scheme must minimize both [13].…”
Section: Resultsmentioning
confidence: 99%
“…In other words, DRESS codes enjoy the repair efficiency of the replication scheme, and are suitable for high-churn environments with frequent node joins/leaves (e.g., peer-to-peer distributed storage systems). Friedman et al [34] evaluated the efficiency of DRESS codes in practical peer-to-peer environments, and showed that the concatenated scheme can achieve better features than each of the methods separately. Moreover, Itani et al [35], [36] investigated the optimal repair cost of DRESS code based data storage systems, where they proposed efficient genetic algorithms for the single node failure and multiple node failure scenarios respectively.…”
Section: B Dress Code and Fractional Repetition Codementioning
confidence: 99%
“…In order to avoid the above dichotomy and offer a more flexible design, replicated erasure codes have been proposed [8]. In the latter, each of the p + q chunks may be replicated r times.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate the fundamental problem of expected data persistency of replicated erasure codes when the storage nodes permanently leave the system and erase their locally stored data. This study is related and motivated by the work of [8]. Namely, the general family of redundancy schemes for distributed storage systems, called replicated erasure codes was introduced in [8].…”
Section: Introductionmentioning
confidence: 99%